ANKS3 co-localises with ANKS6 in mouse renal cilia and is associated with vasopressin signaling and apoptosis in vivo in mice - Delestré, Laure; Hoffmann, Sigrid (PLOS ONE, 2015)
Mutations in Ankyrin repeat and sterile alpha motif domain containing 6 (ANKS6) play a causative role in renal cyst formation in the PKD/Mhm(cy/+) rat model of polycystic kidney disease and in nephronophthisis in humans. A network of protein partners of ANKS6 is emerging and their functional characterization provides important clues to understand the role of ANKS6 in renal biology and in mechanisms involved in the formation of renal cysts. Following experimental confirmation of interaction between ANKS6and ANKS3 using a Yeast two hybrid system, we demonstrated that binding between the two proteins occurs through their sterile alpha motif (SAM) and that the amino acid 823 in rat ANSK6 is key for this interaction. We further showed their interaction by co-immunoprecipitation and showed in vivo in mice that ANKS3 is present in renal cilia. Downregulated expression of Anks3 in vivo in mice by Locked Nucleic Acid (LNA) modified antisense oligonucleotides was associated with increased transcription of vasopressin-induced genes, suggesting changes in renal water permeability, and altered transcription of genes encoding proteins involved in cilium structure, apoptosis and cell proliferation. These data provide experimental evidence of ANKS3-ANKS6 direct interaction through their SAM domain and co-localisation in mouse renal cilia, and shed light on molecular mechanisms indirectly mediated by ANKS6 in the mouse kidney, that may be affected by altered ANKS3-ANKS6 interaction. Our results contribute to improved knowledge of the structure and function of the network of proteins interacting with ANKS6, which may represent therapeutic targets in cystic diseases.